Junb regulates arterial contraction capacity, cellular contractility, and motility via its target Myl9 in mice - Licht, Alexander; Nübel, Tobias; Feldner, Anja; Jurisch-Yaksi, Nathalie; Marcello, Marco; Demicheva, Elena; Hu, Jun-Hao; Hartenstein, Bettina; Augustin, Hellmut; Hecker, Markus; Angel, Peter; Korff, Thomas; et al. (The journal of clinical investigation, 2010)
Cellular contractility and, thus, the ability to alter cell shape are prerequisites for a number of important biological processes such as cytokinesis, movement, differentiation, and substrate adherence. The contractile capacity of vascular smooth muscle cells (VSMCs) is pivotal for the regulation of vascular tone and thus blood pressure and flow. Here, we report that conditional ablation of the transcriptional regulator Junb results in impaired arterial contractility in vivo and in vitro. This was exemplified by resistance of Junb-deficient mice to DOCA-salt–induced volume-dependent hypertension as well as by a decreased contractile capacity of isolated arteries. Detailed analyses of Junb-deficient VSMCs, mouse embryonic fibroblasts, and endothelial cells revealed a general failure in stress fiber formation and impaired cellular motility. Concomitantly, we identified myosin regulatory light chain 9 (Myl9), which is critically involved in actomyosin contractility and stress fiber assembly, as a Junb target. Consistent with these findings, reexpression of either Junb or Myl9 in Junb-deficient cells restored stress fiber formation, cellular motility, and contractile capacity. Our data establish a molecular link between the activator protein–1 transcription factor subunit Junb and actomyosin-based cellular motility as well as cellular and vascular contractility by governing Myl9 transcription.
Gesehen am 14.03.2023